(untitled) - Andrews, Malcolm; Malcolm Andrews (Oxford,New York, 1999)
What is landscape? How does it differ from "land?" Does landscape always imply something to be pictured, a scene? When and why did we begin to cherish images of nature? What is "nature?" Is it everything that isn't art, or artifact? By addressing these and many other questions, Landscape and Western Art explores the myriad ideas and images of the natural world in Western art since the Renaissance
Keywords: Landscapes in art; Landscapes; Nature (Aesthetics)